(untitled) (Књижевна историја — часопис за науку о књижевности, 2025)
Starting from the observation that Louisa May Alcott’s most famous novel Little Women (1868) is an unconventional “girls’ novel”, this paper offers evidence that it actually represents a fusion of transcendental and sentimental ideas. The initial hypothesis is that Alcott attempts to translate Emerson’s concept of self-reliance, which is male, into its female version. Moreover, the vision of the novel is also in accordance with Bronson Alcott’s views on child-rearing and education. However, in order to make their philosophical ideas more appealing and down-to-earth, the novel combines them with the sentimental worldview, resulting in a pragmatic form of Transcendentalism. In dealing with the issues of self-actualisation, children upbringing, education, and work, as reflected in Little Women, the conclusion emerges that not only the vision of the novel is shaped by both the transcendental and sentimental ideology, but also that some of the concepts of these ideologies coincide. The paper argues that it is precisely this unusual combination of progressive ideas and everyday issues in the novel that continues to spark the interest of both readers and critics almost 160 years after its publication.